Bronchotomy for metal foreign object removal in pediatric airway - Andres Felipe Marín Giraldo; Carlos Felipe Bustillos Serna; Luis Mauricio Figueroa Gutiérrez; Juan Felipe Osorno Moncayo (Elsevier, 2023)
Foreign Body Aspiration (FBA) is a common medical emergency in children, demands a prompt diagnosis through clinical manifestations and radiological studies, to prevent complications and mortality. We present a case of a one-year-old female patient that accidently aspirated a foreign metal object into her airway. Two unsuccessful extractions through bronchoscopies were attempted, therefore a bronchotomy was carried out to remove the foreign object. The patient was uneventfully discharged after being monitored and receiving systemic antibiotics in the general hospitalization ward for seven days.